Business Development Strategy of Expedition Companies: A Case Study - Prima Fithri; Hilma Raimona Zadry; Debi Ansuly (Management Institute Faculty of Economics Universitas Andalas, 2019)
The development of information and communication technology which is rapidly increasing now causes changes in people's behavior in shopping. This is supported by the increasing number of online shopping or e-commerce businesses in the community. PT Pos Indonesia as a business entity engaged in sending letters and packages also has considerable opportunities in this business. However, the strength of PT Pos Indonesia at this time cannot be said to be good, because, based on the results of a survey conducted on 30 samples of people and students in the city of Padang showed that only about 7% of people chose PT Pos Indonesia as a courier for shipping goods. This research was conducted to design the right business strategy for PT Pos Indonesia to compete in the package or goods delivery business using Strengths Weaknesses Opportunities and Threats (SWOT) analysis. From the results of the strategic plan made, it can be concluded that PT Pos Indonesia Padang is in a good internal and external environment. However, PT Pos Indonesia's position compared to its competitors is weak. Based on Quantitative Strategic Planning Matrix (QSPM), the proposed strategy given to PT Pos Indonesia Padang in such company conditions is an intensive strategy.